Evidence for Early Human Presence at High Altitudes in the Ötztal Alps (Austria/Italy). Issue 3 (2014) - Kutschera, Walter; Patzelt, Gernot; Wild, Eva Maria; Haas-Jettmar, Barbara; Kofler, Werner; Lippert, Andreas; Oeggl, Klaus; Pak, Edwin; Priller, Alfred; Steier, Peter; Wahlmüller-Oeggl, Notburga; Zanesco, Alexander
Abstract : The present article reports on the results and interpretation of a total of 235 radiocarbon dates from Alpine sites in the Ötztal region. Out of these, 88 age determinations were performed on equipment and artifacts associated with the Neolithic Iceman (discovered in 1991), and on a variety of plant and animal specimens collected at his discovery site. Since the material was dispersed over a larger area, 14 C dates were important to establish the deposition time of the respective samples. About half of the samples fall into the time period where the Iceman lived, documenting synchronous deposition, whereas the others spread out over several thousand years before and after his lifetime. The other set of samples (147) were collected along the Ötztal Valley to the north, with a few samples collected also south of the Alpine watershed. The samples were mainly from soil profiles and peat bogs above the present-day timberline. Overall, the analysis of the data indicates human presence in these high regions of the Alps throughout the Holocene. While the older botanical and archaeological finds indicate activities of hunting and foraging, the younger ones (after ∼5000 BC) point to an intensification of pasturing. This suggests that early human activity was concentrated at altitudes where natural pastures were found, which were probably more favorable than locations at the bottom of the valleys where flooding and other hazards existed. Early users may have come from south of the water divide spreading into the northern regions, particularly during the summer season. It is possible that the Iceman perished at one of his crossings over the probably well-known high-altitude mountain pass due to reasons not yet fully resolved.